2023
DOI: 10.3390/ijms24065770
|View full text |Cite
|
Sign up to set email alerts
|

Radiation from UV-A to Red Light Induces ROS-Dependent Release of Neutrophil Extracellular Traps

Abstract: Neutrophils release decondensed chromatin or extracellular traps (NETs) in response to various physiological and pharmacological stimuli. Apart from host defensive functions, NETs play an essential role in the pathogenesis of various autoimmune, inflammatory, and malignant diseases. In recent years, studies have been performed on photo-induced NET formation, mainly activated by UV radiation. Understanding the mechanisms of NET release under the influence of UV and visible light is important to control the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…and Arzumanyan et al. showed that red, blue and long-wave UV light can induce NET formation in neutrophils ( 31 , 32 ). These findings suggest that flavins can directly capture electrons excited by visible and invisible light spectrum to generate some ROS.…”
Section: Discussionmentioning
confidence: 99%
“…and Arzumanyan et al. showed that red, blue and long-wave UV light can induce NET formation in neutrophils ( 31 , 32 ). These findings suggest that flavins can directly capture electrons excited by visible and invisible light spectrum to generate some ROS.…”
Section: Discussionmentioning
confidence: 99%
“…NET formation is activated not only by UV-A but also by the three visible light spectra, blue, green, and orange, in a dose-dependent manner. Light-induced NETosis was found to proceed via NADPH oxidase and PAD4 ( Arzumanyan et al, 2023 ). Furthermore, it has been revealed that in an asthma model, PM2.5 aggravates NQO1-induced mucus hypersecretion through the release of NETs ( He et al, 2021 ).…”
Section: The Role Of Lifestyle Diet Microbiome Genetics and Environme...mentioning
confidence: 99%